PENGARUH DAYA TARIK WISATA, HOTEL RESTORAN,BIRO PERJALANAN TERHADAP PENYERAPAN TENAGA KERJA DAN PENDAPATAN PERKAPITA - Anjasmara, Kadek Deny; Setiawina, Nyoman Djinar (Buletin Studi Ekonomi, 2019)
Abstract: The Effect of Tourism Attractions, Hotel Restaurants, Travel Agencies on Labor Absorption and Per capita Income The purpose of this study is analyze:1) direct effect oftourist attraction,hotel restaurant,travel agency on employment. 2)direct effect oftourist attraction,hotel restaurant,travel agency and employment on percapita income. 3)indirect effects of tourist attraction,hotel restaurant,travel agencyon percapita income through employment. The analysis technique uses path analysis. Results of the simultaneous direct effecttourist attraction,hotel restaurant,travel agency on employmentis positive significant effect, and will have positive implications for tourism sector employment. The results of the simultaneous direct effect between tourist attraction,hotel restaurant,travel agency, and employment on income percapita had positive significant . The results of this analysis have implications for increasing percapita income in the districts / cities of the Province of Bali. The results of indirect effect of tourist attraction,hotel restaurant,travel agencyon the percapita income through employment with a causal step, Hotel restaurant and travel agency had a positive significant effect on percapita income.Effect of tourist attraction on percapita income through employmenthad positive influence not significant. Keywords: tourist attraction; hotel-restaurant; travel agency; employment; percapita income.